Contrasting intensity of aragonite dissolution and dolomite cementation in glacial versus interglacial intervals of a subtropical carbonate succession. Issue 5 (17th March 2022) - Reuning, Lars; Deik, Hanaa; Petrick, Benjamin; Auer, Gerald; Takayanagi, Hideko; Iryu, Yasufumi; Courtillat, Margot; Bassetti, Maria‐Angela
Abstract: Aragonite and high‐Mg calcite are abundant in modern, neritic carbonate systems but almost absent in their fossil counterparts. Dissolution of these metastable mineral phases commonly leaves no visible trace in the sedimentary record, compromising the derivation of palaeoenvironmental information from the rock record. The upper 25 m of Integrated Ocean Drilling Program (IODP) Site U1460 on the outer ramp of the western Australian Shelf were investigated to study shallow burial (tens of metres) marine diagenesis in organic‐carbon poor sediments using microscopic, total organic carbon, biomarkers and mineralogical analysis in combination with porewater geochemistry. Aragonite dissolution is negligible at the seafloor but intensifies ca 5 m below, even though bulk porewaters are supersaturated for aragonite. This apparent contradiction likely results from dissolution in undersaturated microenvironments. Aragonite dissolution below 5 to 6 m is on average more intense in interglacial compared to glacial intervals. The presence of disseminated framboidal pyrite and porewater results indicate that minor sulphate reduction is active at IODP Site U1460. Sulphate reduction is probably limited by the low organic matter content ( ca 0.2%). It is well‐known from the literature that incipient sulphate reduction can lead to a drop in pH and consequently to carbonate dissolution. It is therefore assumed that the slightly higher concentration of organic matter in the interglacial intervals allowed increased aragonite dissolution during sulphate reduction compared to glacial beds. Low amounts of dolomite cement (<15%) start to form at the same depth (5 to 6 m) as aragonite dissolution intensifies. Dolomite formation and aragonite dissolution also show covariance on a metre‐scale below 5 to 6 m, indicating that a low carbonate saturation state might enhance dolomite formation. This mechanism provides an indirect link between dolomite formation, aragonite dissolution and orbital cycles. The outcome of this study, therefore, contributes to a better understanding of differential diagenesis in marine carbonates.